Amino acid repeats avert mRNA folding through conservative substitutions and synonymous codons, regardless of codon bias. Issue 12 (December 2017) - Barik, Sailen
Abstract: A significant number of proteins in all living species contains amino acid repeats (AARs) of various lengths and compositions, many of which play important roles in protein structure and function. Here, I have surveyed select homopolymeric single [(A)n] and double [(AB)n] AARs in the human proteome. A close examination of their codon pattern and analysis of RNA structure propensity led to the following set of empirical rules: (1) One class of amino acid repeats (Class I) uses a mixture of synonymous codons, some of which approximate the codon bias ratio in the overall human proteome; (2) The second class (Class II) disregards the codon bias ratio, and appears to have originated by simple repetition of the same codon (or just a few codons); and finally, (3) In all AARs (including Class I, Class II, and the in-betweens), the codons are chosen in a manner that precludes the formation of RNA secondary structure. It appears that the AAR genes have evolved by orchestrating a balance between codon usage and mRNA secondary structure. The insights gained here should provide a better understanding of AAR evolution and may assist in designing synthetic genes.